Tecnologías del saber musical en Río de Janeiro en el siglo XIX: el caso de la viola - Varoni de Castro, Renato Moreira (El oído pensante, 2020)
This article discusses methodological strategies for dealing with historical sources in (ethno)musicology research. I name this approach “technologies of musical knowledge” and besides a review of the importance of technologies for the development of (ethno)musicology, I support my perspective through visual examples from my own investigation about the violas in nineteenth century Rio de Janeiro. I argue that despite the myriad of sources available, including iconographic representation (drawings and paintings), travelogues, chronicle and fictional literature, musical scores and tutors; their ethnographic information can only emerge out of a process of interpretation that involves a full assessment of the representational medium in which the data is presented. In other words, I defend that a thorough analysis and interpretation of musical documents depends on the awareness of the technological enablements and constraints in which the historical representations are inscribed.